1978
DOI: 10.1097/00000658-197811000-00019
|View full text |Cite
|
Sign up to set email alerts
|

The Stapled Gastrointestinal Tract Anastomosis

Abstract: Performance of gastrointestinal anastomosis by means of surgical stapling devices has achieved popularity in the last decade even though no detailed study has been reported comparing complications following the stapled anastomosis with those following hand sutured procedures performed by the same surgeons. We have reviewed 812 operative procedures on the gastrointestinal tract performed in one hospital over a four year period. Stapled anastomoses were performed in 472 with 13 (2.8%) complications related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

1981
1981
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(14 citation statements)
references
References 9 publications
1
12
0
1
Order By: Relevance
“…In experiment 3, the wide technique of FETEA with EndoGIA 60 blue had a broad circumference and good patency, whereas buttressing did not influence the circumference. These results suggest that the modification proposed by Chassin et al [3] produces a larger anastomosis at the initial phase. We examined acute phase data in this study.…”
Section: Discussionsupporting
confidence: 56%
“…In experiment 3, the wide technique of FETEA with EndoGIA 60 blue had a broad circumference and good patency, whereas buttressing did not influence the circumference. These results suggest that the modification proposed by Chassin et al [3] produces a larger anastomosis at the initial phase. We examined acute phase data in this study.…”
Section: Discussionsupporting
confidence: 56%
“…However, some articles have pointed out that stapling anastomoses are unfavorable under certain circumstances [4]. Inflammatory bowel disease is thought to be one of the risky conditions for anastomotic complications [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…The other 24 found that patients with stapled anastomoses were less likely to experience dehiscence than those with sutured anastomoses, particularly in the presence of preoperative septic peritonitis. Reports 2529 on this topic in the human medical literature have conflicting results. In light of the high mortality rates associated with intra-abdominal complications in veterinary patients, and considering the financial burden to owners when a second surgery is required, it is desirable to identify the anastomotic technique with the lowest rate of intra-abdominal complications regardless of differences in preoperative variables, pathogenesis of the condition that necessitates surgery, or anatomic site of the anastomosis.…”
mentioning
confidence: 99%